Implementation of the Smart Village Policy to Enhance Public Services in Srimulyo Village, Piyungan Sub-district, Bantul Regency, Yogyakarta Special Region - Domi Sella; Sari Viciawati Machdum (Cita Konsultindo Research Center, 2024)
The Smart Village Policy is a program aimed at strengthening village governance and development (P3PD). It is designed to enhance village institutional capacity and improve governance to provide excellent services to the village community. Srimulyo Village has successfully implemented this policy and this study aims to describe its implementation in enhancing services. Edwards III's theory is used to observe the elements of communication, resources, disposition, and bureaucratic structure. This research is a qualitative descriptive study that examines village officials, facilitators, digital ambassadors, digital village cadres, and the management of the village digital community space as the subjects of analysis. Informants were selected using a